1997
DOI: 10.1002/eji.1830270941
|View full text |Cite
|
Sign up to set email alerts
|

The mannose receptor functions as a high capacity and broad specificity antigen receptor in human dendritic cells

Abstract: Dendritic cells, in contrast to B lymphocytes, must be able to efficiently internalize a diverse array of antigens for processing and loading onto major histocompatibility complex (MHC) class II molecules. Here we characterize the mannose receptor pathway in dendritic cells and show that mannose receptor-mediated uptake of antigens results in a approximately 100-fold more efficient presentation to T cells, as compared to antigens internalized via fluid phase. Immunocytochemistry as well as subcellular fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
200
2
9

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(223 citation statements)
references
References 44 publications
10
200
2
9
Order By: Relevance
“…It has been previously shown that mannosylated antigens are internalized and processed following the endocytic pathway, leading to enhanced MHC class II presentation of antigenic peptides [4,5]. In our studies, we show that MD greatly enhances the delivery of OVA into both MHC class I-and II-presentation pathways in BMDC (Fig.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It has been previously shown that mannosylated antigens are internalized and processed following the endocytic pathway, leading to enhanced MHC class II presentation of antigenic peptides [4,5]. In our studies, we show that MD greatly enhances the delivery of OVA into both MHC class I-and II-presentation pathways in BMDC (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…Uptake of antigens via these receptors on the APC surface is followed by delivery into the endolysosomal pathway, leading to MHC-class II presentation [4]. In comparison to antigens internalized via the fluid phase (e.g., pinocytosis), this pathway of antigen uptake in DC results in a considerable increase of efficiency in antigen presentation and T cell stimulation [5][6][7][8]. For instance, it was shown that antigen uptake mediated by mannosebinding receptors increased antigen presentation to T cells up to 100-fold [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This 205-kD protein contains C-type lectin domains and is a homologue to the MR CD206. In fact, both the MR [47,48] and DEC-205 [49,50] mediate antigen uptake. CD205 expression on human DC is up-regulated upon maturation, and this endocytic receptor is involved in both antigen uptake and processing.…”
Section: Discussionmentioning
confidence: 99%
“…This observation could be applied to antibodies or aptamers -siRNA conjugates. Targeting macrophages, that are the principal source of MMP-12 production, can be assessed by exploiting the mannose-binding receptor that mediates the non-opsonic phagocytic uptake by macrophages [126] and the endocytosis of soluble glycoconjugates leading to enhanced uptake of ligands [127]. However, other classes of phagocytic-inducing receptors also expressed on macrophage surface can be investigated.…”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%